ASSESSMENT OF SOME BIOCHEMICAL AND IMMUNOLOGICAL MARKERS IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOUS: A CASE-CONTROL STUDY - Noor Nayyef Oudah; Malaa M. Taki; Aymen Radhi Habeeb (European Science Publishing, 2025)
Background: Systemic Lupus Erythematosus (SLE) is a complex autoimmune disease frequently involving renal complications, most notably lupus nephritis. Early detection and monitoring of renal involvement are critical for effective disease management. Therefore, the current study designed to evaluate a biochemical (urea, creatinine, uric acid) and immunological (anti-dsDNA, PR3-ANCA) markers in SLE patients to evaluate their potential as diagnostic and prognostic indicators of renal dysfunction. Methods: A case-control study was conducted involving 68 participants (33 males, 35 females), divided into patient and healthy control groups. Serum levels of urea, creatinine, uric acid, anti-dsDNA antibodies, and PR3-ANCA were measured using standardized assays. Statistical comparisons were made using unpaired t-tests with a significance threshold of p < 0.01. Results: SLE patients showed significantly elevated levels of urea (101.1 ± 6.6 vs. 35.4 ± 1.2 mg/dL), creatinine (1.8 ± 0.6 vs. 0.5 ± 0.1 mg/dL), and uric acid (6.9 ± 1.2 vs. 4.5 ± 0.7 mg/dL) compared to controls (all p < 0.0001). Similarly, anti-dsDNA (45 ± 6.9 vs. 12.9 ± 1.8 IU/mL) and PR3-ANCA (2.6 ± 0.8 vs. 0.5 ± 0.3 IU/mL) levels were significantly higher in patients, indicating heightened autoimmune and vasculitis activity. Conclusion: The concurrent elevation of renal and immunological markers suggests that kidney dysfunction in SLE patients is closely linked to underlying autoimmune mechanisms. Anti-dsDNA and PR3-ANCA may serve as valuable biomarkers for diagnosing and monitoring renal involvement in SLE.
Keywords: SLE, Nephritis, dsDNA, RFTs, PR3-ANCA.